ISOLASI DAN UJI POTENSI BAKTERI DIAZOTROF NON SIMBIOTIK ASAL TANAH KEBUN KELAPA SAWIT DENGAN APLIKASI TANDAN KOSONG DAN LIMBAH CAIR PABRIK KELAPA SAWIT - Huryatul Islam; Nelvia Nelvia; Delita Zul (Jurnal Agroteknologi, 2019)
This study aimed was to isolate non-symbiotic N-fixation bacteria from oil palm plantations fertilized with empty fruit bunch (EFB) and palm oil mill effluent (POME) and to analyze their potency. The soil samples were taken by purposive sampling method from 4 different treatments are mixed application (EFB + POME), EFB application, POME application and without application (C), and each location was taken 3 times. Isolation of non-symbiotic N-fixation bacteria was perfomed by using NFb and Ashby's media. The parameters observed were bacterial cells number, number of isolates and their potency. The cells number of non-symbiotic N fixation bacteria at the application sites Mixed> POME application> EFB application> C. A total of 18 isolates were isolated and potentially as a nitrogen fixing bacteria characterized by the ability of isolates to change the color of the NFb medium from green to blue and form pellicle. The highest potential isolates are NFBC232, NFBK21, and NFBC33.